Challenges in the treatment of femoral osteomyelitis - Mohd Yusof, Nazri (2018)
Introduction Fixation of pathological fracture of femur is difficult because its anatomy is different from tibia. The proximal part of femur which is the head, neck and trochanter cannot be fix with the ordinary external fixation. The shaft of femur also is bowed and the proximity of the contralateral thigh makes inserting of the ring fixator difficult. The hip and knee joint that joints the femur to the pelvis and tibia also requires special consideration when fixing the femoral fracture. I will share few cases to illustrate the challenges in managing pathological fracture of femur secondary to osteomyelitis. Case 1 A 25-year old man had an infection following plate osteosynthesis of femur 6 months after injury. The plate was removed during debridement and the fracture was stabilised with the uniplanar external fixation. However, 4 months later the fracture got displaced and repeated debridement and acute shortening was done using LRS. The LRS was removed after 4 months following fracture union. Case 2 A 22-year old man had chronic osteomyelitis of distal femur following open supracondylar fracture for 4 years. He also had knee joint stiffness due to bad intra articular fracture and quadriceps muscle injury. He was treated with multiple debridement with antibiotics beads but infection persist. He then developed pathological fracture and subsequently treated with bone resection and bone transport using a hybrid LRS. Case 3 A 15-year old orang asli (aborigine) boy was admitted with pathological fracture of midshaft of femur. The MRI shows long oblique fracture with large collection of pus in the shaft together with long segment of necrotic bone and femoral neck fracture. 10 cm of distal femur was resected and the bone was overlap and stabilised with the LRS. The femoral neck was stabilised with 7.5 mm cancellous screw. Femoral lengthening was started 2 months later after the infection was controlled. The LRS was removed 9 months later. Unfortunately 4 months later,he had fracture at the thin bone segment following a fall and was treated with locked plate and bone graft. Case 4 A 16 –year old boy on remission following chemotherapy for leukaemia was treated for osteomyelitis of both femur and tibia. He also had septic arthritis of left hip with subluxation. He underwent repeated hip arthrotomy over a period of 3 months with high dose of IV antibiotic. Since he continued to have sinus discharge, an MRI was performed which revealed necrotic left femoral head. Finally, during last operation arthrotomy revealed necrotic femoral head and was resected. The acetabular cavity was filled with custom made local antibiotic base on antibiotic sensitivity. Case 5 A 21-year old man was treated with acute shortening followed by lengthening following infected open fracture. 16 month later the LRS was removed. However, the regenerate fractured 1 week after removal of LRS and he was treated with interlocking nail 2 months later. Conclusion Modern monolateral external fixation and local antibiotic are effective in managing femoral osteomyelitis. However, be aware that re-fracture may occur after removal of external fixation.